The in-situ testing and modeling on sealing strength deterioration of lithium-ion pouch cell. (February 2021) - Zhang, W.; Wei, Y.C.; Cheng, M.X.; Liu, Y.M.; Sun, H.
Highlights: An in-situ testing conducted to investigate the traction-separation relationship. A modified CZM developed to evaluate the sealing strength degradation. A small constant tensile load leading to adhesive strength deterioration and fracture. The fracture energy reduction accounting for the sealing strength degradation. Abstract: The pouch cell is of great potential application among a variety of power batteries, because of its higher energy density and lower weight. Due to the existence of internal gas generation in the long lifetime of the pouch cell, the slowly increasing internal gas pressure will cause a time-dependent fracture in its package sealing edge. This process significantly affects the remaining useful life and reliability. In this paper, an in-situ experiment was performed and a modified cohesive zone model (CZM) was proposed to describe the seal strength degradation behavior. Firstly, the in-situ tensile test was conducted to measure the sealing strength curve, and the exponential CZM was used to characterize the constitutive relation of the sealing area based on the load-displacement data. Secondly, constant stress accelerated degradation tests (CSADT) were carried out to simulate the degradation process, where the action of gas pressure on sealing area was converted to accelerated tensile load. Then, the exponential CZM was modified to account for the strength degradation behavior with the effect of constant load duration, based on the traction-separation relationship. The fracture energy was calculated by area integral under the load-displacement curve, whose reduction represented the degradation phenomenon. Finally, the proposed model was validated by the testing data, and a good agreement was observed.